2019
DOI: 10.29303/jku.v8i2.339
|View full text |Cite
|
Sign up to set email alerts
|

Korelasi antara Jumlah Limfosit Total dan Limfosit Cd4+ pada Pasien HIV/AIDS di RSUD Provinsi NTB

Abstract: Latar belakang: HIV (Human Immunodeficiency Virus) merupakan suatu jenis retrovirus yang berasal dari famili lentivirus. Virus ini memiliki kemampuan khusus yaitu merubah komponen RNA (Ribonucleic Acid) menjadi DNA (Deoxyribonucleic Acid). Virus HIV merupakan jenis virus yang menyerang sel limfosit CD (Cluster Differentiation) 4+ . Negara Indonesia merupakan negara kepulauan yang masih memiliki keterbatasan dalam melakukan pemeriksaan CD4+. Hitung jumlah limfosit total dapat dijadikan alternatif menggantikan p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…Decreased CD4 cell count results in reduced TLC as evidenced by Resindra et al, that TLC can be used as a replacement check for CD4 cell count in monitoring HIV infection. 15 The results of research conducted by Sanjaya's et al, also support the existence of a moderate correlation of TLC with CD4 cell count in all aspects of study. 16 There are differences in the results of the research found both conducted abroad and in Indonesia as well as the limited research on the relationship between TLC and CD4 in Indonesia, especially in East Nusa Tenggara.…”
Section: *Corresponding Authormentioning
confidence: 53%
“…Decreased CD4 cell count results in reduced TLC as evidenced by Resindra et al, that TLC can be used as a replacement check for CD4 cell count in monitoring HIV infection. 15 The results of research conducted by Sanjaya's et al, also support the existence of a moderate correlation of TLC with CD4 cell count in all aspects of study. 16 There are differences in the results of the research found both conducted abroad and in Indonesia as well as the limited research on the relationship between TLC and CD4 in Indonesia, especially in East Nusa Tenggara.…”
Section: *Corresponding Authormentioning
confidence: 53%